General Mykhailo Omelianovych-Pavlenko - organizer and theoretic of Ukrainian Free Cossacks movement - Sergii Hozuvatenko (Cхід, 2013)
Military-organizational activity of General Mykhailo Omelianovych-Pavlenko concerning establishment and organization of Ukrainian Free Cossacks movement is investigated. Outstanding Ukrainian military activist, army commander in the period of national-liberation movement was among the organizers and commanders of Free Cossacks movement in the period of Ukrainian revolution of 1917-1920 and between wars in emigration, during World War II, and in postwar on theterritoryofCzechoslovakiaandGermany.